Innovation, Firm Size, and a Firms Age in Tourism - Pawlicz, Adam; Molski, Andrzej; Liszka, Wojciech (Studia Oeconomica Posnaniensia, 2017)
The aim of the paper is to present the impact of selected characteristics of tourism enterprises, especially the age and size on their level of innovation and an analysis of the theoretical and practical aspects of public support to start-ups on the tourist market. In the first stage of the study the relevant literature has been reviewed to determine the theoretical evidence for and against public support to start-ups in the context of the specific nature of the tourism market. In the second stage qualitative methods have been used such as an expert panel of restriction analysis. This papers deals only with the most important, from the point of view of economic practice, and areas of justifying public support to start-ups on the tourist market. It has to be underlined that a full theoretical analysis of the merits of supporting start-ups can contribute to a better distribution of a substantial amount of public aid allocated to support its development. This paper constitutes a pioneering attempt to the issue of supporting start-ups in the tourist market and the impact of the size and age of tourism enterprises on their innovation activities. The main findings from the study can be summarized as follows: there is no relationship between a firm's size and age on their innovation behaviour. Moreover, no specificity of innovations on the tourism market could be identified. So there is no economic rationale for the creation of tourism specific subsidies that are aimed at fostering innovations in start-ups.